2015
DOI: 10.1208/s12249-015-0458-y
|View full text |Cite
|
Sign up to set email alerts
|

Use of Polyvinyl Alcohol as a Solubility-Enhancing Polymer for Poorly Water Soluble Drug Delivery (Part 1)

Abstract: Abstract. Polyvinyl alcohol (PVAL) has not been investigated in a binary formulation as a concentrationenhancing polymer owing to its high melting point/high viscosity and poor organic solubility. Due to the unique attributes of the KinetiSol® dispersing (KSD) technology, PVAL has been enabled for this application and it is the aim of this paper to investigate various grades for improvement of the solubility and bioavailability of poorly water soluble active pharmaceutical ingredients. Solid amorphous dispersi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 55 publications
2
34
0
Order By: Relevance
“…Particularly, it was shown Przybyłek et al, 2017) that compounds containing polar OH and COOH groups are excellent methylxanthines solubility enhancers. Solubility increase in the presence of hydrophilic compounds is consistent with many experimental data (Brough et al, 2015;Savjani et al, 2012;Thiry et al, 2017b). It is understandable that hydrophilic excipients will also improve the dissolution profile.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Particularly, it was shown Przybyłek et al, 2017) that compounds containing polar OH and COOH groups are excellent methylxanthines solubility enhancers. Solubility increase in the presence of hydrophilic compounds is consistent with many experimental data (Brough et al, 2015;Savjani et al, 2012;Thiry et al, 2017b). It is understandable that hydrophilic excipients will also improve the dissolution profile.…”
Section: Introductionsupporting
confidence: 87%
“…This is in accord with chemical intuition and pharmaceutical drug delivery strategies (Brough et al, 2015;Ghanbarzadeh et al, 2016;Kalepu and Nekkanti, 2015;Maggi et al, 2013;Sareen et al, 2012;Savjani et al, 2012;Serajuddin, 1999;Sruti et al, 2013) that differences in polarities between drug and excipient is a main driving force toward dissolution. Many examples of such cases can be found in the literature, including cocrystals but also other types of solid mixtures such as inclusion complexes with cyclodextrins (Dua et al, 2011;M Badr-Eldin et al, 2013;Thiry et al, 2017aThiry et al, , 2017b and dispersions with soluble polymers (Brough et al, 2015;Choi and Park, 2017;Ibrahim et al, 2010;Maggi et al, 2013;Six et al, 2004;Thiry et al, 2017a). Noteworthy, Guha et al, (2011), found that APIs can be classified in terms of their kinetic solubility values using different hydrophilicity indices.…”
Section: Selection Of Appropriate Molecular Descriptorsupporting
confidence: 75%
“…Although not specifically formulated for 3D printing, several other investigators used PVA as the matrix for the solid dispersion of drugs and observed variable miscibility between drugs and polymer by DSC and powder X-ray diffraction (PXRD) analyses. 28,[40][41][42] Thus, it is apparent that the method of preparation and the drug-polymer miscibility are important aspects of using PVA for 3D printing.…”
Section: Introductionmentioning
confidence: 99%
“…The paper [23] describes that different grades of PVA as a stabilizer for membrane-bound and membrane-encapsulated ferments can significantly affect the activity of the latter. At the same time, the paper [24] describes that molecular weight and hydrolysis degree of PVA affect bioavailability and solubility of some poorly-soluble drugs. Using model itraconazole as a model drug, it was determined that the use of some grades of PVA is preferable for aqueous media.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%